Patterns and Risk Factors of Traumatic Brain Injuries in Pediatric Patients Visiting the Emergency Room in Saudi Arabia: A Cross-sectional Analysis - Abdulsalam Aleid; Thekra Alqahtani; Norah Almasaad; Salah Mustafa; Manar Alqahtani; Khalid Alsuwat; Mohammed Asiri; Abbas Al Mutair; Khalid Almulhim (Dr. Sulaiman Al Habib Medical Journal)
Introduction: Traumatic brain injuries (TBIs) in pediatric patients are a pressing public health concern, with limited data in the Saudi Arabian context. This study aimed to identify patterns, risk factors, and clinical outcomes associated with TBIs among pediatric patients visiting emergency rooms in Saudi Arabia. Methods: A cross-sectional analytical study was conducted, involving 1,030 pediatric patients admitted to emergency departments of King Fahad Hospital in Hofuf, Almoosa Hospital in Hofuf, King Fahad Hospital in Dammam, King Fahad Hospital in Madina, King Faisal Hospital in Alahsa, King Faisal Specialist Hospital in Riyadh, and King Abdulaziz University Hospital in Jeddah. The age of the patients was predominantly within the range of 18–24 years, constituting 58.5% of the total sample. Data were collected through standardized questionnaires and analyzed using Chi-square tests and descriptive statistics. Results: Falls were the predominant cause of TBIs, accounting for 69.8% of cases. No significant correlation was found between age and TBI severity (P = 0.072). However, the cause of TBI significantly influenced clinical outcomes (P < 0.05). Conclusion: While age did not significantly impact the severity of TBIs, the cause of the injury played a critical role in clinical outcomes. These findings provide a foundation for targeted preventive measures and interventions.